(untitled) (AL MUNAZHZHARAH, 2024)
Marriage dispensation is a waiver for someone who wants to get married but is hindered by age because he has not yet reached the age of marriage who is submitted to the Religious Court. Many marriages are experienced by minors as regulated by law no. 16 of 2019 has not been allowed to carry out marriage, causing parents to apply for a marriage dispensation at the Religious Courts because the marriage was rejected by the Office of Religious Affairs because the child has not yet reached the age of marriage.This study aims to determine the considerations of the Kediri Regency Religious Court judges in resolving marriage dispensation cases, as well as the reasons for marriage dispensations that are often proposed.There are several problems in this research that the author wants to examine, namely: what is the reason for the large number of applications for marriage dispensation at the Religious Courts of Kediri Regency, what is the basis for the judge’s juridical considerations in determining the application for marriage dispensation at the Kediri Regency Religious Court. The study involves qualitative methods, using the date-gathering techniques of observation and interview and documentation. The data comes in the primary and secondary data data and then the data is analyzed through the data reduction stage, data verification, data presentation, data analysis and finally drawn conclusions. The results showed There are many reasons that marriage dispensation is often filed at the Religious Court. Kediri, There are internal factors such as out of wedlock, the desire of the child themselves wanting to marry, low education and economic factors. As well as external factors such as the customary and worrisome factors of a parent toward a child’s advancing relationship with his or her mate. The judge’s consideration at the Kediri Regency Religious Court in determining the application for marriage dispensation is based on the following considerations: 1). Administrative completeness, 2). Article 53 Kompilasi Hukum Islam (KHI) on pregnant marriage, 3). There are no barriers to marriage between children and their partners as stated in Article 8 of Law no. 1 of 1974 concerning Marriage, and 4). Principles of benefits and drawbacks, 5). Maintain public trust in the courts, especially the Religious Courts.